Classification method of cultivated land based on UAV visible light remote sensing - Xu, Weicheng; Lan, Yubin; Li, Yuanhong; Luo, Yangfan; He, Zhenyu (International Journal of Agricultural and Biological Engineering, 2019)
The accurate acquisition of the grain crop planting area is a necessary condition for realizing precision agriculture. UAV remote sensing has the advantages of low cost use, simple operation, real-time acquisition of remote sensor images and high ground resolution. It is difficult to separate cultivated land from other terrain by using only a single feature, making it necessary to extract cultivated land by combining various features and hierarchical classification. In this study, the UAV platform was used to collect visible light remote sensing images of farmland to monitor and extract the area information, shape information and position information of farmland. Based on the vegetation index, texture information and shape information in the visible light band, the object-oriented method was used to study the best scheme for extracting cultivated land area. After repeated experiments, it has been determined that the segmentation scale 50 and the consolidation scale 90 are the most suitable segmentation parameters. Uncultivated crops and other features are separated by using the band information and texture information. The overall accuracy of this method is 86.40% and the Kappa coefficient is 0.80. The experimental results show that the UAV visible light remote sensing data can be used to classify and extract cultivated land with high precision. However, there are some cases where the finely divided plots are misleading, so further optimization and improvement are needed. Keywords: UAV, visible band, remote sensing, extraction of cultivated land area, object oriented method DOI: 10.25165/j.ijabe.20191203.4754 Citation: Xu W C, Lan Y B, Li Y H, Luo Y F, He Z Y. Classification method of cultivated land based on UAV visible light remote sensing. Int J Agric & Biol Eng, 2019; 12(3): 103–109.